2021
DOI: 10.3390/ijerph18052292
|View full text |Cite
|
Sign up to set email alerts
|

The Synergistic Process of Improvement in Cognitive Behavioral Therapy for Major Depression

Abstract: Background: There is a substantial lack of qualitative research concerning individual cognitive behavioral therapy (CBT) for patients with major depressive disorder (MDD). In the present study, we wanted to explore how patients suffering from MDD experience improvement in CBT. Method: Patients with MDD (N = 10) were interviewed at therapy termination with semi-structured qualitative interviews. The transcripts were analyzed using a thematic analysis approach. Results: We identified three elements that were rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
(58 reference statements)
0
4
0
1
Order By: Relevance
“…In two previous articles on the same patient material we found that both patients who had received CBT and PDT wanted tools to help them out of the depression [39,40]. By exploring the metaphor of tools more closely when it is used by the patient, the therapist may get a better understanding of what the patient actually needs.…”
Section: Tools: What Patients Need To Improvementioning
confidence: 97%
“…In two previous articles on the same patient material we found that both patients who had received CBT and PDT wanted tools to help them out of the depression [39,40]. By exploring the metaphor of tools more closely when it is used by the patient, the therapist may get a better understanding of what the patient actually needs.…”
Section: Tools: What Patients Need To Improvementioning
confidence: 97%
“…We used a reference list to analyze ME and categorize conceptual metaphors. Specifically, the list contains the following studies: (1) Literature on depression metaphors ( Hughes-Hammer et al, 1998 ; McMullen and Conway, 2002 ; Pritzker, 2003 , 2007 ; Schoeneman et al, 2004 ; Charteris-Black, 2012 ; Refaie, 2014 ; Kauschke et al, 2018 ; Leis et al, 2019 ; Yoon et al, 2019 ; Beck, 2020 ; Tong, 2020 ; Coll-Florit et al, 2021 ; Malkomsen et al, 2021 ; Munday et al, 2021 ; Taylor-Jackson and Moustafa, 2021 ) (2) List of metaphors ( Lakoff et al, 1991 ) (3) Oxford guide to metaphors in CBT ( Stott et al, 2010 ) …”
Section: Methodsmentioning
confidence: 99%
“…(1) Literature on depression metaphors ( Hughes-Hammer et al, 1998 ; McMullen and Conway, 2002 ; Pritzker, 2003 , 2007 ; Schoeneman et al, 2004 ; Charteris-Black, 2012 ; Refaie, 2014 ; Kauschke et al, 2018 ; Leis et al, 2019 ; Yoon et al, 2019 ; Beck, 2020 ; Tong, 2020 ; Coll-Florit et al, 2021 ; Malkomsen et al, 2021 ; Munday et al, 2021 ; Taylor-Jackson and Moustafa, 2021 )…”
Section: Methodsunclassified
“…We have previously shown that the improvement process is experienced after therapy as a gradual, non-linear and slow process involving many elements that interact synergistically (33). Patients seldom refer to just one particular element of therapyrather, "it's the whole package" that stimulates improvement.…”
Section: Identifying Synergistic and Cumulative Effectsmentioning
confidence: 99%
“…In fact, the differences in how improvement in CBT and PDT is experienced seem to have diminished in the years that have passed after therapy ended. We have previously interviewed patients who received CBT and PDT in the MOP project just a few weeks after therapy ended (33,42). After three years, patients who received CBT highlight fewer CBT specific elements than a few weeks after therapy.…”
Section: Diminishing Importance Of the Therapeutic Approachmentioning
confidence: 99%